2021
DOI: 10.1101/2021.01.06.425300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glycogen Synthase Kinase 3 regulates the genesis of the rare displaced ganglion cell retinal subtype

Abstract: Glycogen Synthase Kinase 3 (GSK) proteins (GSK3α and GSK3β) are key mediators of signaling pathways, with crucial roles in coordinating fundamental biological processes during neural development. Here we show that the complete loss of GSK3 signaling in mouse retinal progenitors leads to microphthalmia with broad morphological defects. Both proliferation of retinal progenitors and neuronal differentiation are impaired and result in enhanced cell death. A single wild-type allele of either Gsk3α or Gsk3β is able … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Interestingly, dRGCs also sharply concentrate in the same region slightly extending toward the temporal quadrant. In the mouse retina, dRGC neurogenesis is under the control of Glycogen Synthase Kinase 3 and may contribute to binocular vision as they project to the ipsilateral thalamus [ 72 , 73 ]. The functional role of dRGCs in TLGS remains to be explored.…”
Section: Discusionmentioning
confidence: 99%
“…Interestingly, dRGCs also sharply concentrate in the same region slightly extending toward the temporal quadrant. In the mouse retina, dRGC neurogenesis is under the control of Glycogen Synthase Kinase 3 and may contribute to binocular vision as they project to the ipsilateral thalamus [ 72 , 73 ]. The functional role of dRGCs in TLGS remains to be explored.…”
Section: Discusionmentioning
confidence: 99%
“…One interesting note is the possible mislocalization of cone cells bodies in the ONL as well as the presence of RBPMS + cells in the INL of the Chx10-Cre Lsd1 fl/fl mice. These cells may be displaced retinal ganglion cells, an extremely rare retinal subtype (Dräger and Olsen, 1981;Buhl and Dann, 1988;Doi et al, 1994;Nadal-Nicolás et al, 2014;Kisseleff et al, 2021); however, further validation via co-labeling of multiple antibodies and retrograde labeling beyond the scope of this present study are needed. We also investigated synaptic connections by co-labeling Bassoon and Ribeye, which are two components of the photoreceptors ribbon synapses (Brandstätter et al, 1999;Schmitz et al, 2000).…”
Section: Resultsmentioning
confidence: 84%
“…ERK signaling negatively regulates L-Maf, an important factor needed to promote the differentiation of lens cells from the neural retina [53]. GSK-3 plays an important role in neural and retinal development [54,55] and is also involved with a variety of other signaling pathways (Wnt, hedgehog, insulin and notch) [56][57][58][59]. Inhibited by Akt during non-canonical signaling, Marchena et al also found that inhibition of GSK-3 by treatment with small molecule inhibitors led to retinal cell neuroprotection in a retinitis pigmentosa model [60].…”
Section: Tgf-β/bmp Signaling: Neural and Retinal Developmentmentioning
confidence: 99%